Experiences of People Living with HIV and Tuberculosis amid Fear, Guilt, and Silence: A Qualitative Study - Amirudin, Ikhwan; Waluyo, Agung; Sujianto, Untung; Akbar, M Agung; Nursasi, Astuti Yuni; Ayubi, Dian (Nurse Media Journal of Nursing, 2026)
Background: People living with HIV–TB (PLHIV–TB) continue to experience persistent stigma, fear, guilt, and silence that shape their psychosocial wellbeing and social interactions. HIV–TB represents a double burden that intensifies stigma and moral judgment, particularly within sociocultural and religious contexts. However, the lived experiences of PLHIV–TB in Indonesia remain insufficiently explored, despite the country’s unique cultural and religious dynamics. Understanding these contextualized experiences is essential for strengthening holistic, culturally responsive, and stigma-sensitive HIV–TB care.Purpose: This study aimed to explore experiences of PLHIV-TB amid fear, guilt, and silence within the Indonesian sociocultural context.Methods: A descriptive phenomenological design was employed, with 20 PLHIV-TB purposively selected from Lampung, Palembang, Depok, and Yogyakarta between January and June 2025. Data were collected through in-depth, semi-structured interviews lasting 45–70 minutes and analyzed using NVivo software with Colaizzi’s method. Trustworthiness was ensured through member checking, peer debriefing, and reflexivity.Results: Six themes captured the essence of participants’ experiences: (1) living under constant fear of exposure, (2) choosing silence as protection, (3) bearing the weight of guilt and moral judgment, (4) loneliness amid social disconnection, (5) struggling with faith and moral reconciliation, and (6) searching for meaning and self-acceptance. Participants’ narratives revealed a transformation from concealment and shame toward spiritual reconciliation and dignity through emotional and faith-based resilience.Conclusion: The lived experiences of people living with HIV–TB in Indonesia are shaped by intertwined dynamics of fear, guilt, and silence within a context of pervasive stigma. At the same time, some individuals demonstrate adaptive processes that reflect a complex journey from suffering to meaning-making and self-acceptance. These findings underscore the need for stigma-sensitive, psychosocial, and spiritually informed interventions to support holistic HIV–TB care.